(untitled) (International Journal of Engineering and Computer Science, 2017)
An investigation of viscous dissipation possessions on MHD unsteady heat and mass transfer flow past an exponentially accelerated vertical plate all the way through a porous medium with changeable temperature with heat source has been considered the dimensionless essential equations are solved by resources of the perturbation technique. Resulting non-dimensional velocity, temperature and concentration summary are then accessible graphically for diverse standards of the parameters entering into the problem. Finally, the personal property of the pertinent parameters on the skin-friction coefficient, the speed of heat transfer (Nusselt number) and the speed of mass transfer (Sherwood number), which are of physical interest, are accessible graphically.